Dampak pandemi covid-19 terhadap usaha mikro di indonesia: tantangan dan solusi - Khoiriyah, Lailatul (Maliki Interdisciplinary Journal, 2025)
The COVID-19 pandemic has had a significant impact on the microenterprise sector in Indonesia. Social restrictions imposed to reduce the spread of the virus caused many microentrepreneurs to struggle with survival, experiencing a drastic decline in income and halting operations. Additionally, many entrepreneurs were unprepared for the digital transformation, worsening their challenges in conducting business online. On the other hand, government policies intended to help SMEs, such as low-interest loans and grants, were not always effective in reaching all micro-enterprise owners. This study analyzes the impact of the pandemic on micro-enterprises in Indonesia and the adaptation strategies implemented by entrepreneurs in facing this crisis. The findings indicate that digitalization, product diversification, and adaptation to government policies are crucial for the sustainability of micro-enterprises. Therefore, the government needs to improve access to technology and provide education as well as simplify procedures to accelerate the recovery of this sector.